Biomarkers of Exposure and Effects for Assessing Toxicological Risk of Endocrine Disrupters in Top Predators of the Mediterranean Sea - FOSSI, M. C.; CASINI, S.; MARSILI, L.; ANCORA, S.; MORI, G.; NERI, G.; AUSILI, A.; ROMEO, T.; MOSCATELLI, A.; NOTARBARTOLO DI SCIARA, G. (Marine Ecology, 2002)
Endocrine Disrupting Chemicals (EDCs) have the potential to alter hormone pathways that regulate reproductive processes in wildlife and fisheries. In this research the unexplored hypothesis that Mediterranean top predator species (such as large pelagic fish and marine mammals) are potentially at risk due to EDCs is investigated. In the Mediterranean environment, top predators accumulate high concentrations of polyhalogenated aromatic hydrocarbons (PHAHs) and toxic metals, incurring high toxicological risk. Here we illustrate the need to develop sensitive biomarkers for evaluation of toxicological risk in top marine predators (Xiphias gladius, Thunnus thynnus thynnus) and non-lethal techniques, such as non-destructive biomarkers, for the hazard assessment of threatened species exposed to EDCs, such as marine mammals (Stenella coeruleoalba, Tursiops truncatus, Delphinus delphis and Balaenoptera physalus).